Surveillance of Viruses in Varroa destructor Samples Collected from Honey Bee Colonies in Ontario, Canada, between 2015 and 2019 - Morfin, Nuria; Kozak, Paul; Ledger, Lisa; You, Qiu; Bell-Rogers, Patricia; Zechel, Jennifer; Krishnamurthy, Aparna; Slavic, Durda; Guzman-Novoa, Ernesto; Cai, Hugh Y. (Journal of Apicultural Science, 2022)
parasitism is associated with extreme honey bee ( ) colony losses in the northern hemisphere. causes severe damage, including a decrease in bee longevity and immunosuppression, and acts as a vector for viruses, such as (DWV-A). The surveillance of viral pathogens in samples is essential to assess risks of emerging virulent viral variants (such as VDV-1) and evaluate their impact on honey bee health. Thus, the objective of this study was to identify viral pathogens in and honey bee samples collected in Ontario, Canada, from 2015 to 2019 with the use of metagenomics and real time PCR (qPCR). DWV-A and VDV-1 had the highest abundance of viral transcripts (7.5 log2 and 5.72 log2, respectively). Acute bee paralysis virus (ABPV) and were also identified. Viral identification and quantification in samples using metagenomics will facilitate the surveillance of viral pathogens. This surveillance technique will assist diagnostic laboratories in delivering timely and accurate diagnoses and risk assessments, which in turn will help honey bee producers to take adequate measures to mitigate the damage caused by and associated viruses.